PERENCANAAN PENANGANAN PERGERAKAN TANAH DENGAN METODE SOLDIER PILE DI STA. 07+100 JALUR PIPA PENYALUR KM. 53 – SKG BONTANG - BUDIMAN, LALU ELHAM (KURVA S JURNAL MAHASISWA, 2018)
Gas Pipeline Right of Ways KM. 53 - Bontang SKG (Gas Compressor Station) owned by PT. Pertamina Gas (Pertagas) has a potential landslide. There are 3 gas pipelines in the line, which are 2 carbon steel pipes with a diameter of 16